Inclusive Early Childhood Education: To What Extent is Inclusion of Academic Benefit to ECD Learners with Intellectual and Learning Disabilities? - Pangeti, Fungayi Fortune; Mapolisa, Tichaona; Chisaka, Bornface Chenjerai (Advances in Social Sciences Research Journal, 2023)
The extent to which inclusion is of academic benefit to ECD learners with intellectual and learning disabilities is a topical subject for discussion among educators. The participatory action research study was conducted to find out the extent to which the inclusive education practices at an ECD Centre in Harare were of academic benefit for learners with intellectual and learning disabilities. Data were generated from seven learners with intellectual and learning disabilities, teachers and parents of the learners, university lecturers and from the school administrator. Our action research cycles included teaching in the respective learner’s classes, as well as observations made on the playground. For triangulation we combined data generated from our interviews with key participants, participant and non-participant observations, and from document analyses. The NVivo data management system was used to code data into emergent themes. We concluded that although the school was open to inclusion, the teachers were not well trained for it, and that the learners could have benefited from a more diverse curriculum to compensate for their academic challenges. Our recommendations following the research were that both the parent government ministry, and the school administration could do more for the teachers in terms of training in inclusive education practices. We also recommended that for future research opportunities, the study could be extended to include an investigation into inclusive education practices as they relate to learners with intellectual disabilities as they transition from primary school to secondary school.